Sistema de aviso e alerta: aplicação ao Concelho de Torres Novas - Ribeiro, Manuel (2022)
Climate change has caused major catastrophes in places where it was thought not to be expected. Monitoring and the consequent alert and warning of risk have been a huge challenge for evolved modern societies. For a system that brings together these three concepts to work, it must, above all, know its territory and its threats. For that, technical competence and political will must be aligned. An ideal warning and alert system would be one that could cover the monitoring of all risks and thus allow the authorities to issue warnings to the population, in a timely, assertive, and strictly necessary manner, using the most expeditious channels. The district of Santarém is heterogeneous, as it brings together low and medium intensity territories. In addition, it is characterized by more than two dozen risks identified by each of its member municipalities. This heterogeneity also ends up happening in the various municipal civil protection services, since not all municipalities have a Municipal Civil Protection Coordinator. It is noted that there is no culture of prevention duly disseminated, on the contrary, assistance and emergencies continue to be implemented. This position, created by Decree-law in 2019, could be the catalyst for the implementation of monitoring, warning, and alert systems within the respective municipality. In Torres Novas, it is urgent to create monitoring systems that can produce outputs for the definition and issuance of special warnings and alerts, to the population and civil protection agents, respectively. Currently the only monitoring systems (hydrometric stations) are obsolete and inoperative. This monitoring requires equipment, planning, analysis, and data processing so that warnings and special alerts can be produced, duly corrected, so that they do not have the opposite effect, that of discredit. In addition, municipal services must implement a warning doctrine among the population, especially the most vulnerable to each of the risks. .